In-situ polymerisation of fully bioresorbable polycaprolactone/phosphate glass fibre composites: in vitro degradation and mechanical properties - Chen, Menghao; Parsons, Andrew J.; Felfel, Reda M.; Rudd, Christopher D.; Irvine, Derek J.; Ahmed, Ifty (Elsevier, 2016)
Fully bioresorbable composites have been investigated in order to replace metal implant plates used for hard tissue repair. Retention of the composite mechanical properties within a physiological environment has been shown to be significantly affected due to loss of the integrity of the fibre/matrix interface. This study investigated phosphate based glass fibre (PGF) reinforced polycaprolactone (PCL) composites with 20%, 35% and 50% fibre volume fractions (Vf) manufactured via an in-situ polymerisation (ISP) process and a conventional laminate stacking (LS) followed by compression moulding. Reinforcing efficiency between the LS and ISP manufacturing process was compared, and the ISP composites revealed significant improvements in mechanical properties when compared to LS composites. The degradation profiles and mechanical properties were monitored in phosphate buffered saline (PBS) at 37°C for 28 days. ISP composites revealed significantly less media uptake and mass loss (p<0.001) throughout the degradation period. The initial flexural properties of ISP composites were substantially higher (p<0.0001) than those of the LS composites, which showed that the ISP manufacturing process provided a significantly enhanced reinforcement effect than the LS process. During the degradation study, statistically higher flexural property retention profiles were also seen for the ISP composites compared to LS composites. SEM micrographs of fracture surfaces for the LS composites revealed dry fibre bundles and poor fibre dispersion with polymer rich zones, which indicated poor interfacial bonding, distribution and adhesion. In contrast, evenly distributed fibres without dry fibre bundles or polymer rich zones, were clearly observed for the ISP composite samples, which showed that a superior fibre/matrix interface was achieved with highly improved adhesion.